Communication Strategy of Sharia Pawnshop of Palu Plaza in Introducing Program of Easy Ways to Baitullah - Kaddi, Sitti Murni; Al-Kafiah, M. Kafrawi; Adrian, Donal; Erdiyansyah, (Technium Social Sciences Journal, 2020)
This research aims to determine Communication Strategy of Sharia Pawnshop of Palu Plaza in introducing program of an Easy Ways to Baitullah. This research applied a qualitative descriptive approach which aimed to systematically describe the communication strategy of Pawnshop Syraiah of Palu Plaza. Data collection techniques include in-depth interviews and observation. The results show that in introducing Arrum Hajj products related to the easy ways to Baitullah, Sharia Pawnshop of Palu Plaza uses communication strategy consisting of (a) delivering messages; highly credible employees who are able to persuade customers, namely Leader, Public Relations and Marketing of Sharia Pawnshop of Palu Plaza; (b) Messages related to Easy Ways to Baitullah such as making it easier for customers to make initial payments by providing a guarantee of 3.5 grams of precious metal, or ordinary gold of 4 to 5 grams and administrative costs as the initial process for managing Arrum Hajj, managing files through offline and online as well as the ability of the Leader, Public Relations and Marketing Officer in composing persuasive sentences using Indonesian and local languages, both face to face and media; and (c) Using social media such as Facebook, Instagram, Twitter and others. Furthermore, another conventional media such as face to face communication. The use of messages from these two media can be in form of standard language and local languages such as dialect and local language of Kailinesse.